The Current Problems of the Teaching and Learning Dulcimer Performance at Capital Normal University, China - Jiayi, An; Pattananon, Nicha (Journal of Modern Learning Development, 2023)
The research objectives were (1) To study the current problems in the performance and teaching of the dulcimer at the Capital Normal University. (2) To analyze the playing skills of the dulcimer and to propose solutions based on the existing problems in dulcimer teaching. The methodology was qualitative research which collected data from interviews. Key informants were 8 dulcimer students and 10 music teachers from the Conservatory of Music at the Capital Normal University. The research findings found that (1) Teachers of the dulcimer Program can arrange group classes according to different teaching contents, objectives, and target groups to make the teaching content clear, and effective. There are several group lessons: chamber music lessons, music appreciation lessons, practical theatre arts lessons, music theory lessons, and expert lectures. (2) the teachers teach the basic knowledge and playing techniques of the dulcimer in class, but teaching the correct way to play dulcimer needs to be addressed. Many dulcimer students report problems with the instrument when playing dulcimer.